2018
DOI: 10.1038/s42003-018-0029-3
|View full text |Cite
|
Sign up to set email alerts
|

Vortices enable the complex aerobatics of peregrine falcons

Abstract: The peregrine falcon (Falco peregrinus) is known for its extremely high speeds during hunting dives or stoop. Here we demonstrate that the superior manoeuvrability of peregrine falcons during stoop is attributed to vortex-dominated flow promoted by their morphology, in the M-shape configuration adopted towards the end of dive. Both experiments and simulations on life-size models, derived from field observations, revealed the presence of vortices emanating from the frontal and dorsal region due to a strong span… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 20 publications
4
19
0
1
Order By: Relevance
“…Finally, during the M-shape configuration that is adopted towards the end of dive, the stoop was characterized by vortex dominated flow. [6] The experiments and simulations revealed that vortices rose from the frontal and dorsal regions due to strong spanwise flow promoted by the forward sweep, as shown in Fig. 8.…”
Section: Numerical Simulations Using Computational Fluid Dynamicsmentioning
confidence: 87%
See 4 more Smart Citations
“…Finally, during the M-shape configuration that is adopted towards the end of dive, the stoop was characterized by vortex dominated flow. [6] The experiments and simulations revealed that vortices rose from the frontal and dorsal regions due to strong spanwise flow promoted by the forward sweep, as shown in Fig. 8.…”
Section: Numerical Simulations Using Computational Fluid Dynamicsmentioning
confidence: 87%
“…During this phase, the arm opens up further into the horizontal plane and the wings are aligned in a way that the bird appears to be in an M-shaped planform when seen from above. [6] In this phase, the trailing edge of wing detaches from the body, such that there is a forward sweep in the in-board section and aft sweep in the outboard section of the wing. [4] As the falcon goes deep into pull out maneuver, there is a reduction in sweep angle in the outboard section of the wing.…”
Section: Cuppedshapementioning
confidence: 99%
See 3 more Smart Citations